Microbial O2 consumption as a function of pore structure in soils of sorghum, switchgrass, and prairie vegetation systems - Poulamee Chakraborty; Andrey Guber; Alexandra Kravchenko (Vadose Zone Journal)
Abstract Microscale O2 availability in soil, a main factor influencing microbial processing of soil carbon and nitrogen, is a function of O2 diffusion and microbial O2 consumption. While O2 diffusivity is widely studied, it is difficult to quantify the rate of microbial O2 consumption (MO). In this study, we quantified the MO using O2 microsensor profiling to compare MO in different soils and vegetation systems while manipulating the soil pore structure. Soil samples were collected from three bioenergy vegetation systems, sorghum (Sorghum bicolor L. Moench), switchgrass (Panicum virgatum L.), and prairie, at an experimental site in Southeast Michigan, and from switchgrass and prairie systems at two sites in South and North Wisconsin. We prepared soil cores with two contrasting pore structures, that is, large (>30 µm Ø) pore‐dominated soil (LP) and small (<10 µm Ø) pore‐dominated soil (SP), from the same 1‐ to 2‐mm soil size fraction. We quantified MO (nmol O2 cm−3 s−1) using a microprofiler with an oxygen (OX‐100 µm) microsensor (Unisense) pre‐ and post‐38‐day incubation. Across all studied systems, there was a trend for a decrease in SP MO post‐incubation, suggesting a change in microbial metabolism to lower O2 utilization. However, sizeable microbial O2 consumption continued in the LP soils, further corroborated by a positive correlation between the C‐CO2 emission rate and the post‐incubation MO, highlighting that LP provided a better physical microenvironment for the soil microbes.